Desarrollo de habilidades STEM y su relación con la formación en Ciudadanía Ambiental en las aulas de Educación Preescolar - Niño Gutiérrez, Elizabeth Magaly; Gómez Torres, Francisco Hernando; Briceño Pira, Lilia (Educación y Ciudad, 2025)
This research aims to show the results of a systematization of early childhood education experiences carried out in La Felicidad public school between 2018 and 2023. This was an educational project based on the STEM perspective, within a context dubbed living classroom. The results evidence a pedagogical model connected by an experiential and situated perspective that fosters STEM education during early childhood by undertaking pro-environmental actions deployed from urban ecological contexts, within the framework of the natural sciences. This is an innovative, practical, and contextual alternative that also facilitates the interaction between the school and the community. The conclusions indicate that the STEM approach can be interwoven with environmental citizenship education processes in the formal education context by means of living classrooms, in order to foster an active and conscious commitment to the environment. This applies not only to early childhood, but also to other levels. In addition, this work highlights the importance of the aforementioned integration in children, given their disposition to explore the world around them, which constitutes a unique opportunity to incorporate concepts from the natural sciences, mathematics, engineering, and technology through the lens of environmental care. By promoting this union, the foundations for an ethically responsible citizenship are laid, highlighting the importance of a multidisciplinary approach to environmental citizenship education, wherein educational processes are not limited to separate disciplines but also incorporate a holistic approach.